Designing living environments with adults with autism. Issue 2 (1st April 2014) - Lowe, C.; Gaudion, K.; McGinley, C.; Kew, Alex
Abstract : Purpose: – The purpose of this paper is to explore how a people-centred, design-led approach to the different needs and aspirations of adults with autism could help inform the design of space, objects and activities for individuals in their own homes to enhance everyday life experiences. There are dozens of studies that have reported the health benefits associated with good design and the Kingwood Trust set out to research what that might mean for the adults with autism it supports. Design/methodology/approach: – The paper describes three projects: Housing Design, Garden Design and Exploring Sensory Preferences whose design interventions were realised through a process of design ethnography, to include and work with the people that Kingwood support who have limited verbal speech and learning disabilities. Participatory observation, co-design workshops, interviews, visual probes and mapping tools were created to gather insights about how a person perceives and engages with the physical environment, with a particular focus on their sensory sensitivities and special interests. Findings: – The outcome of the project is a holistic, design-led approach to identifying the sensory preferences and special interests of adults with autism to inform the design of residential accommodation. A second project will be published at a later date, which will test and evaluate the effectiveness of the design interventions described in this paper as part of a PhD by practice supported by Kingwood Trust. Originality/value: – Autistic adults with limited verbal speech and additional learning disabilities, are often excluded from design research. This paper bridges this gap by selecting and adapting design methods that invite the people that Kingwood support to be active participants within the design process. The revised DSM-5 is an important milestone that puts the sensory environment back onto the roadmap within autism research, however the relationship between people with autism and the physical environment is a relatively under-researched area. This paper bridges this gap in research and illustrates how an autistic person's interaction and reaction to their home environment, can create understanding, tangible insights and clues to inform the design and adaptation of environments to reduce triggers of anxiety, making them more comfortable, enjoyable and meaningful for that person.